CD4+CD25+ Regulatory T Cells Control Innate Immune Reactivity after Injury - Thomas J. Murphy; Niamh Ni Choileain; Yan Zang; John A. Mannick; James A. Lederer (2005)
Abstract Major injury initiates a systemic inflammatory response that can be detrimental to the host. We have recently reported that burn injury primes innate immune cells for a progressive increase in TLR4 and TLR2 agonist-induced proinflammatory cytokine production and that this inflammatory phenotype is exaggerated in adaptive immune system-deficient (Rag1−/−) mice. The present study uses a series of adoptive transfer experiments to determine which adaptive immune cell type(s) has the capacity to control innate inflammatory responses after injury. We first compared the relative changes in TLR4- and TLR2-induced TNF-α, IL-1β, and IL-6 production by spleen cell populations prepared from wild-type (WT), Rag1−/−, CD4−/−, or CD8−/− mice 7 days after sham or burn injury. Our findings indicated that splenocytes prepared from burn-injured CD8−/− mice displayed TLR-induced cytokine production levels similar to those in WT mice. In contrast, spleen cells from burn-injured CD4−/− mice produced cytokines at significantly higher levels, equivalent to those in Rag1−/− mice. Moreover, reconstitution of Rag1−/− or CD4−/− mice with WT CD4+ T cells reduced postinjury cytokine production to WT levels. Additional separation of CD4+ T cells into CD4+CD25+ and CD4+CD25− subpopulations before their adoptive transfer into Rag1−/− mice showed that CD4+CD25+ T cells were capable of reducing TLR-stimulated cytokine production levels to WT levels, whereas CD4+CD25− T cells had no regulatory effect. These findings suggest a previously unsuspected role for CD4+CD25+ T regulatory cells in controlling host inflammatory responses after injury.